Respostas

A melhor resposta!
2014-08-19T17:31:01-03:00
X² + 5x + 6 = 0
Δ = (5)² - 4.(1).(6)
Δ = 25 - 24
Δ = 1
x = - (5) +/- √1 ÷ 2.(1)
x = -5 +/- 1 ÷ 2
x'= -5 + 1 ÷ 2 = -4 ÷ 2 = - 2
x"= -5 -1 ÷ 2 = -6 ÷ 2 = - 3

x² - 7x + 12 = 0
Δ = (-7)² - 4.(1).(12)
Δ = 49 - 48
Δ = 1
x = - (-7) +/- √1 ÷ 2.(1)
x = 7 +/- 1 ÷ 2
x'= 7+1 ÷ 2 = 8 ÷ 2 = 4
x"= 7-1 ÷ 2 = 6 ÷ 2 = 3

x² + 5x + 4 = 0
Δ = (5)² - 4.(1).(4)
Δ = 25 - 16
Δ = 9
x = - (5) +/- √9 ÷ 2.(1)
x = - 5 +/- 3 ÷ 2
x' = -5 +3 ÷ 2 = -2 ÷ 2 = - 1
x" = -5 -3 ÷ 2 = -8 ÷ 2 = - 4

3 5 3